Financial System Architecture - Boot, Arnoud W. A.; Thakor, Anjan V. (Review of Financial Studies, 1997)
This article builds a theory of financial system architecture. We ask: what is a financial market, what is a bank, and what determines the economic role of each? Starting with basic assumptions about primitives—the types of agents and the nature of informational asymmetries—we provide a theory that explains which agents coalesce to form banks and which trade in the capital market. It is shown that borrowers of higher observable qualities access the financial market. Moreover, a financial system in its infancy will be bank-dominated, and increased financial market sophistication diminishes bank lending.